Decarbonizing the cement industry in Latin America and the Caribbean: A comprehensive review of strategies, barriers, and policies - Andrés André Camargo-Bertel; Diego Hincapie; Victor Pugliese; Arturo Gonzalez-Quiroga; Oscar Pupo-Roncallo (Energy Conversion and Management: X)
Decarbonizing the cement industry is key to reducing greenhouse gas emissions in the industrial sector and achieving sustainable development goals in Latin America and the Caribbean. The region faces economic, regulatory, and technical challenges that must be addressed to facilitate this transition. This article analyzes strategies, barriers, and policies to drive the decarbonization of this sector, assessing their applicability and impact. The study employed a two-stage methodology: first, a data analysis phase involving the collection of greenhouse gas emissions data and key performance indicators; second, a comprehensive review of scientific literature, sectoral roadmaps, and national commitments to identify decarbonization strategies, along with their associated costs, barriers, and policies. Four main strategies were identified: material efficiency, energy efficiency, fuel switching, and renewable energy integration, with CO2 abatement costs ranging from 10 to 45 USD/t CO2, depending on strategy. Additionally, electrification, industrial symbiosis, and carbon capture involve higher costs, with carbon capture ranging from 60 to 100 USD/t CO2. The analysis also evidences research and policy development gaps, highlighting the need to establish consistent regulatory frameworks, foster collaboration among countries, and design financial incentives tailored to local conditions. The results show the importance of a collaborative approach that integrates governments, industries, and the academic sector to overcome existing barriers and promote the adoption of clean technologies. These efforts entail updating sectoral roadmaps, boosting intersectoral cooperation, and developing public policies that respond to the realities of the region.